Sustainability criteria for green building material selection in the malaysian construction industry - Al-Atesh, E. (Springer Science and Business Media Deutschland GmbH, 2021)
A Green building material (GBM) is an environmentally friendly, health-promoting, recycled and high-performance construction materials that affect the selection of materials for all three sustainability pillars (3Ps). The lack of proper instructions for GBM and the difficulty in adjusting GBM sustainability criteria become a challenge for GBM selection. Different strategies have been implemented to meet current and future requirements. This study mainly focused on the GBM criteria selection, through literature review, and expert judgement. A total of three main criteria and 32 sub-criteria have been found. Hence, this study provides sustainable assessment criteria for GBM selection in the Malaysian construction industry. Â© The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2021.